The historical formation of the Arab nation : a study in identity and consciousness - A A Duri; Conrad, Lawrence I. (Routledge Library Editions: The Arab Nation, 2012)
This book is a comprehensive examination of the historical process of social formation that gave rise to the communal consciousness of the Arab nation and determined its sense of identity. It aims to provide a historical context for the assessment of prevailing concepts and suggests hypotheses for the development of modern Arab consciousness. The book firstly traces Arab origins and the formation of Arab societies after the emergence of Islam, assessing the perspectives and factors that shaped the rise of the Arab nation in both practical and intellectual terms. It then examines the
Keywords: Nationalism : Arab countries; Arabism; Arab countries : History : 1798-